Bi5: An Autoethnographic Analysis of a Lived Experience Suicide Attempt Survivor Through Grief Concepts and ‘Participant’ Positionality in Community Research - amelia elias noor (Social Sciences)
This paper explores suicidality and suicide research from an autoethnographic analysis framed through grief concepts. Self-identifying as a Muslim in the United States, the author explains how lived experiences being racialized through Islamophobia, identifying as a genderfluid non-binary woman, being socially biracial, holding a postpartum bipolar diagnosis, and being connected to a diaspora, are critical elements to develop a deeper sociocultural understanding of suicide. Grief concepts that are used to analyze these themes include disenfranchised grief, ambiguous loss, anticipatory grief, and secondary loss. While these grief concepts are understood as part of the author’s embodied lived experience as an individual, there is also a collective grief that is explored through the author’s bilingual experience with Arabic as it relates to the topics of suicide and genocide occurring in the Arabic-speaking diaspora located in Gaza, Palestine. A conceptual framework is offered to make sense of the author’s lived experience by both incorporating and challenging existing academic perspectives on suicide and research. The emic, or insider, perspective is contextualized such that it may hold implications beyond the individual author, such as for U.S. Muslims and other hard-to-reach populations. A positionality statement demonstrates the author’s reflexivity of being an insider ‘participant’–researcher in conducting transformative research approaches with the U.S. Muslim community. Further directions are shared for scholars with lived experience who may seek to utilize comparable individual or collaborative autoethnographic approaches with such majority-world communities.